Radical Prostatectomy in High-Risk Prostate Cancer Patients: Results of a Single- Institution Study - Virote Chalieopanyarwong; Worapat Attawettayanon; Watid Kanchanawanichkul; Choosak Pripatnanont (Journal of Health Science and Medical Research (JHSMR), 2018)
Objective: To evaluate long-term outcomes of radical prostatectomy and bilateral pelvic lymph node dissection (RP) for high-risk prostate cancer (PC). Material and Method: A retrospective review of high-risk PC patients who received RP, identified from medical records. We collected data from Songklanagarind Hospital, Prince of Songkla University from 2007 to 2015. The Kaplan-Meier method and Cox proportional regression models were used to analyze clinical recurrence (CR) and biochemical recurrence (BCR). Results: In 79 patients, the median follow-up was 27.2 months. The 3-year and 5-year biochemical free survival in men with high-risk PC were 67.7% and 62.9% respectively. Multivariate analysis shows that pathologic stage 3a (hazard ratio=4.87; 95% confidence interval=1.01-23.38) was independently associated with cancer control. Conclusion: Data support the belief that RP has a place in the treatment of high-risk PC. RP was a long-term cancer control in patients with high-risk PC. Only pathologic staging was independently associated with cancer control outcome.